PENERAPAN PEMBELAJARAN JARAK JAUH BERBASIS GOOGLE CLASSROOM PADA MASA PANDEMI MAHASISWA STKIP PARIS BARANTAI - Radiatul Adawiah; Radiatul Adawiah (STKIP Paris Barantai, 2020)
The research subjects were 19 students in semester 2 of the 2019/2020 academic year. This research was designed in the form of One Group. The data were collected by using test learning outcomes and observations. Data were analyzed using qualitative descriptive. The results achieved after implementing Google Classroom-based learning on Trigonometry material, which are in the high category on the subject of Trigonometry, obtained an average score for cycle 1 of 75 in cycle 2 of 76.9 then an increase of 11.9 from the ideal score 100. The percentage of student learning completeness in the first cycle was 73.84% of 19 students while in the second cycle the percentage of student learning completeness increased to 89.47% from 19 students. There was an increase in the frequency of student attendance, the activeness and seriousness of students in the teaching and learning process according to the results of observations during the action. From the results of the analysis, it can be concluded that learning with the application of distance learning based on Google Classroom can improve the learning outcomes of second semester students, especially in the Trigonometry subject.